Information and Communication Technologies and productivity in Peruvian agro-export companies in pandemic times - Salazar Sanchez, Fiorella (2025)
This article presents the Information and Communication Technologies (ICT) and their application in the performance of agro-export companies during the period of the pandemic by COVID-19; being the objective of the investigation to describe the incidence of the use of the ICT in the productivity of the companies in the agro-industrial sector. The methodology applied was the systematic review of the literature on each of the constructs, using search criteria in reliable sources such as the Scopus, Redalyc, SciELO databases mainly; thus, inclusion and exclusion criteria were also applied for the selection of information, both for articles and theses. The results obtained showed the importance of the use of ICTs in the growth and development of a country, city or sector, even before the health emergency. After analyzing the information, it was determined that there is a positive impact on companies in the sector when they implemented ICT in their key processes, so it was proposed to develop a full strategic plan as a starting point to forge an innovative culture that facilitates the development of resilience capacity.